Eosinophilic cystitis refractory to steroids successfully treated with benralizumab: A case report - Konstantinou, George N.; Voukelatou, Vasiliki (Frontiers in Allergy, 2023)
We report a case of a 66-year-old male diagnosed with refractory to oral corticosteroids eosinophilic cystitis (EoC). Hematuria was the first and only sign of the disease that was otherwise asymptomatic, and the only abnormal lab finding he had was peripheral eosinophilia (700 cells/μl). Due to cardiovascular issues, an invasive surgical procedure was declined. As an alternative, benralizumab, an anti-IL-5Ra monoclonal antibody with anti-eosinophilic properties, was administered. The patient responded rapidly with clinical and histological complete remission of the EoC four months after benralizumab started. He continued benralizumab 30mg Q4-weeks for 12 months without experiencing any side effects. Four months after the last dose, he is completely healthy with no peripheral eosinophilia. EoC is a rare condition with no standardized treatment. Those with corticosteroid-refractory EoC are eligible for surgery. Benralizumab has an excellent safety profile; therefore, it should be considered before deciding on invasive surgical procedures in selected, refractory to non-specific treatment cases, especially with EoC of unclear etiology. It is unclear if benralizumab may immunomodulate the unknown underlying mechanisms of EoC, considering that EoC did not relapse after benralizumab was deemed eliminated. Further studies are needed to investigate this possibility.